Pemodelan Spasial Tsunami dan Prioritas Mitigasinya di Kecamatan Ambulu Kabupaten Jember: Tsunami Spatial Modelling and Its Mitigation Priorities In Ambulu District Jember Regency - Prasetyo, Emir Dienul Kukuh; Revana, Dano Quinta; Sukmawati, Sri (Universitas Jember, 2024)
Abstract Jember Regency has six sub-districts prone to tsunami disasters, one of which is Ambulu Sub-district. In 1994, it was discovered that two beaches in Ambulu District were affected by the tsunami disaster. The potential for a tsunami disaster on the coast of Ambulu District could affect the safety of tourists and coastal communities in Ambulu District. This research aims to develop mitigation priorities with spatial modeling to help visualize the worst possibility of occurring. The method used is spatial analysis by processing DEM data into slope, then filling in the roughness coefficient value for land cover, followed by modeling tsunami inundation, analyzing affected land use, and using the Analytical Hierarchy Process (AHP) to determine mitigation priorities. The results of this research showed that the tsunami inundation area with a 4 m wave scenario reached 219.09 ha, while the tsunami inundation area with an 11 m wave scenario reached 765.23 ha. The highest area of land affected by tsunami inundation in the 2 scenarios is agricultural land, with an area of 68.71 ha and 343.95 ha. Based on the area obtained, it can help in determining mitigation actions with the help of the AHP method so that priority mitigation directions for the tsunami disaster in Ambulu District, Jember Regency, are obtained, namely the use of tsunami dampening buildings and education, counseling, and public awareness. Keywords: tsunami modeling; mitigation; Analytical Hierarchy Process (AHP); Ambulu Abstrak Kabupaten Jember memiliki enam kecamatan rawan bencana tsunami, salah satunya Kecamatan Ambulu. Pada tahun 1994 diketahui bahwa dua pantai yang berada di Kecamatan Ambulu terdampak bencana tsunami. Adanya potensi bencana tsunami di Pesisir Kecamatan Ambulu dapat mempengaruhi keselamatan wisatawan dan masyarakat pesisir Kecamatan Ambulu. Pada saat yang sama, belum adanya kajian terbaru terkait permodelan spasial inundasi tsunami di Kecamatan Ambulu yang meliputi pembahasan tata guna lahan. Penelitian ini bertujuan untuk menyusun prioritas mitigasi dengan permodelan spasial. Metode yang digunakan adalah analisis spasial dengan pengolahan data DEM menjadi slope, kemudian mengisi nilai koefisian kekasaran pada tutupan lahan, dilanjutkan dengan permodelan genangan tsunami, analisis penggunaan lahan terdampak, dan penggunaan Analytical Hierarchy Process (AHP) untuk penentuan prioritas mitigasi. Hasil dari penelitian ini didapatkan luasan genangan tsunami dengan skenario gelombang 4 m mencapai 219,09 ha, sedangkan luasan genangan tsunami dengan skenario gelombang 11 m mencapai 765,23 ha. Luasan tertinggi penggunaan lahan yang terdampak genangan tsunami dari 2 skenario tersebut adalah lahan pertanian dengan luas 68,71 ha dan 343,95 ha. Hasil penelitian dapat membantu penentuan tindak mitigasi sehingga didapatkan arahan mitigasi prioritas untuk bencana tsunami di Kecamatan Ambulu, Kabupaten Jember yaitu penggunaan bangunan peredam tsunami dan pendidikan, penyuluhan, serta penyadaran masyarakat. Kata kunci: pemodelan tsunami; mitigasi prioritas; Analytical Hierarchy Process (AHP); Ambulu